Towards a resource-driven model of governance: Application to lower-income transition economies - Rick Auty (University of Bonn, Center for Development Research (ZEF), 2003)
Many developing market economies were strongly distorted during the 1960s and 1970s by fashionable policies to force industrialisation and they experienced growth collapses when exposed to the price shocks of the 1970s. In this context, the centrally planned economies were even more highly distorted and they too experienced collapse, albeit a decade later because they were less exposed to trade shocks. Economic reform has had mixed results in both sets of countries and this paper develops a model of governance to explain the main variations among the transition countries. The model incorporates a neglected factor, namely how the scale of the natural resource rents and their socio-economic linkages condition government behaviour. It posits that resource-poor countries are more likely than resource-rich countries to engender a developmental political state, which has sufficient autonomy to pursue coherent policies and also the aim of raising social welfare. The two principal reasons for this are, first, that the governments of resource-poor countries tend to be less distracted from the task of wealth generation by the capture of resource rents and, second, the political economy of resource-poor countries tends to build greater political accountability. The basic model is adapted to explain differential progress with reform among the transition economies by adding to the resource rents two more key initial conditions identified in the literature, namely history (the length of exposure to central planning) and geography (proximity to a dynamic market economy). The model predicts that the most propitious conditions for transition reform arise among the relatively undistorted, resource-poor coastal economies of East Asia, followed by the moderately distorted higher-income (and low-rent) countries of Eastern Europe. The paper shows that the transition countries broadly support the predictions. There are anomalies, however, which require two additional factors to explain them, namely access to geopolitical rents conformity to a regional norm of political state.
Keywords: 330; Political Economy; Übergangswirtschaft; Wirtschaftliche Anpassung; Politisches System; Rohstoffvorkommen; Rent-Seeking; Osteuropa; Ostasien; Kaspisches Meer; Governance-Ansatz; Niedriglohnländer